Fractal analysis of otolith contours and shape for marine fish species discrimination - Fernando Condal; Giulia Guida (Journal of Marine Studies, 2026)
Otolith morphology serves as a powerful tool for species discrimination and ecological studies, yet traditional morphometric approaches often overlook the functionally significant complexity of otolith contours. Here, we apply fractal geometry to analyse 184 sagittal otoliths from five ecologically diverse marine fishes (Merluccius merluccius, Phycis blennoides, Gadus morhua, Lophius piscatorius, and Trachinus araneus) collected from NW Atlantic and Mediterranean waters. Using the Guida et al. (2020) method, we quantified three morphological descriptors: fractal dimension (Df, roughness), circularity (M), and angularity (m). Our results revealed distinct species-specific morpho-spaces. The demersal M. merluccius exhibited the highest contour complexity (Df = 1.06 ± 0.03) and elongation (M = 0.64 ± 0.03), while the other species displayed smoother, more circular otoliths. The strong negative Df-M correlation reflects an evolutionary trade-off between sensory adaptation and hydrodynamic efficiency. These findings establish fractal otolith analysis as an effective taxonomic tool and a window into ecological specialization, with direct applications for fisheries management, paleo-ecological reconstructions, and climate change monitoring in marine ecosystems.